Pengaruh Efektivitas, Efisiensi dan Literasi Keuangan dalam Penggunaan Qris terhadap Inklusi Keuangan Menurut Ekonomi Islam pada Gen-Z di Kota Bengkulu - Dewi Khayyirah Novrianti; Eka Sri Wahyuni; Andi Harpepen (Universitas Muhammadiyah Surabaya, 2026)
This study aims to determine the influence of effectiveness, efficiency, and financial literacy in the use of QRIS on financial inclusion among Generation Z in Bengkulu City. The data was obtained from questionnaires distributed to Generation Z aged 20-24 years in Bengkulu City who had used QRIS. The sample was taken using purposive sampling. This study used a quantitative method with descriptive statistical analysis, validity test, reliability test, classical assumption test, linearity test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the variables of efficiency and financial literacy have a significant relationship with financial inclusion, while the variable of effectiveness does not have a significant effect on financial inclusion among Generation Z in Bengkulu City. Keywords: Effectiveness; Efficiency; Financial Literacy; QRIS; Financial Inclusion